(untitled) (Scientific journal of the Fergana State University, 2024)
The article is devoted to the taxonomic analysis of algae found in the Southern Fergana Canal for the summer season of 2023. As a result of the research, 101 species and varieties of algae belonging to 6 departments, 8 classes, 12 orders, 19 families, and 34 childbirths were identified. Among them Bacillariophyta - 85%, Cyanophyta - 10%, Euglenophyta - 3%, Chrysophyta - 1%, Chlorophyta - 1%, Pyrrophyta - 1%.